PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA TERPADU TIPE CONNECTED POKOK BAHASAN PENCEMARAN AIRDENGAN SUMBER BELAJAR LINGKUNGAN SEKITAR PADA SISWA SMP - As?ari, Hasyim; Kardi, Soeparman; Kirana, Tjandra (Universitas Negeri Surabaya, 2014)
Research development of Integrated Science teaching materials connected type with Dick and Carey model on subject matter water pollution and which aims to improve the learning outcomes of students. The research subject of teaching materials which tested on 32 student of junior high school with design one-group pretest-posttest, and analyzed using descriptive quantitative. The results are validation of teaching materials is valid, learning performance is good. Tests of students learning outcomes were analyzed with N-Gain Increased. Psychomotor skills of students is good), and the teaching materials can develop to students attitudes. The conclusion of this research, that the integrated science teaching materials connected type with environment source learning students in junior high school is feasible and can improve the learning outcomes of studentsTelah dilakukan suatu penelitian pengembangan perangkat pembelajaran IPA terpadu tipe connected dengan model Dick and Carey pada pokok bahasan pencemaran air dan bertujuan untuk meningkatkan hasil belajar siswa SMP. Subyek penelitian perangakat pembelajaran yang diujicobakan pada 32 siswa SMP dengan rancangan one group pretest-posttest,sedangkan analisis data secara deskriptif kuantitatif. Hasil validasi perangkat pembelajaran valid, keterlaksanaan pembelajaran baik. Tes hasil belajar siswa dianalisis dengan N-Gain mengalami peningkatan, kemampuan psikomotor siswa baik, dan perangkat pembelajaran dapat mengembangkan sikap siswa. Simpulan penelitian ini, bahwa perangkat pembelajaran IPA terpadu tipe connected dengan sumber belajar lingkungan sekitar pada siswa SMP layak dan dapat meningkatkan hasil belajar siswa.